From courtroom to clinic: legal cases that changed mental health treatment - Ash, Peter (Cambridge University Press, 2019)
Why do present-day mental health professionals practice the way that they do? Over the past fifty years, a number of landmark court holdings have changed such basic principles as what material is confidential, how civil commitment and involuntary treatment are conducted, and when a therapist has a duty to protect the public from a dangerous patient. Unlike most legal texts, this volume explores these complex principles through the human stories of the litigants involved.